Morphometric analysis of the bottom relief of water areas using GIS (on the example of the area in the Ukrainian Antarctic station "Academic Vernadsky") - Сінна, О. І.; Попов, В. С.; Утєвський, А. Ю. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The research of the bottom relief of water areas is one of the measures of the State target scientific and technical program for conducting research in Antarctica for 2011-2020. It is advisable to analyze spatial distribution of benthic groups. Current experience of research on the bottom relief of the water areas on local sites mainly uses the results of acoustic surveys as a source of data, less often - the data of remote sensing of the Earth and available cartographic materials.The purpose of the article. The purpose of this article is to highlight the methodological approaches to the morphometric analysis of the bottom of the water area by means of GIS (using ArcGIS software complex) tested on the example of the test site of the research. The article also presents the results of modeling and morphometric analysis of the water areas bottom around the Ukrainian Antarctic Station "Academic Vernadsky".Methods. A digital model of the water area bottom relief was constructed according to the echo sound survey. The means of geographic information systems, in particular the ArcGIS software system, are used. Mostly in research we used ArcGIS 3D Analyst, ArcGIS Spatial Analyst, algebra maps tools and other modules.Results. On the basis of DMR, a bathymetric map and three-dimensional models were constructed, transverse channel profiles were constructed, angles of the surface of the surface were calculated, and the depth of the bottom relief dissection was calculated, too. Assessment of the potential accumulation of sediments was carried out. The article is illustrated by the fragments of the results obtained within the test site of the research - Meek Channel Strait between islands Galindez, Grotto and Corner (Argentine Islands, Western Antarctica).Scientific novelty and practical significance. According to inadequate study of the research territory, the detailed relief data of the water area near the Antarctic station "Academic Vernadsky" were obtained and analyzed with GIS for the first time. Results of the development can be used in perspective researches of geochemical links between land and water, for further study of benthic groups.